Do Publicly Disclosed Tax Reserves Tell Us About Privately Disclosed Tax Shelter Activity? - LISOWSKY, PETRO; ROBINSON, LESLIE; SCHMIDT, ANDREW (Journal of Accounting Research, 2013)
ABSTRACT We examine whether public disclosures of tax reserves recently made available through Financial Interpretation No. 48 (FIN 48) reflect corporate tax shelter activities. Understanding this relation is important to corporate stakeholders and researchers keen to infer the aggressive nature of a firm's tax positions from its tax reserve accrual. Our study links public disclosures of tax reserves with mandatory private disclosures of tax shelter participation as made to the Internal Revenue Service's Office of Tax Shelter Analysis. We find strong, robust evidence that the tax reserve is positively associated with tax shelters, while other commonly used measures of tax avoidance are not. Based on out‐of‐sample tests, we also show that the reserve is a suitable summary measure for predicting tax shelters. The tax benefits of tax shelters are economically significant, accounting for up to 48% of the aggregate FIN 48 tax reserves in our sample.